2003
DOI: 10.1128/aac.47.11.3525-3530.2003
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Profile of a Hepatitis C Virus RNA-Dependent RNA Polymerase Benzothiadiazine Inhibitor

Abstract: Recently, a benzo-1,2,4-thiadiazine antiviral agent (C 21 H 21 N 3 O 4 S; compound 4) was shown to be a potent, highly specific inhibitor of the primary catalytic enzyme of the hepatitis C virus (HCV) replicase complex. In this study, we selected for resistance to confirm the mechanism of action for compound 4 in HCV replicon cells. As expected, spontaneous mutations or fluidity in the HCV polymerase (NS5B) coding sequence occurred upon routine passage of the HCV replicon cells in the absence of compound 4. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 18 publications
6
87
1
Order By: Relevance
“…After treatment with concentrations approximating the IC 90 of each compound in combination, only a small number of resistant replicon colonies was obtained, possibly a reflection of the increased complexity of selecting replicon variants bearing multiple resistance mutations and/or of their impaired replication capability (Table 5). Our data showed that dual resistance to thumb I-and to palm-site inhibitors is mediated by mutations Met423Thr and/or Ile482Leu in the thumb domain and mutations in the palm and finger domains (related to palm-site inhibitors), in agreement with previous reports (30,33,40).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After treatment with concentrations approximating the IC 90 of each compound in combination, only a small number of resistant replicon colonies was obtained, possibly a reflection of the increased complexity of selecting replicon variants bearing multiple resistance mutations and/or of their impaired replication capability (Table 5). Our data showed that dual resistance to thumb I-and to palm-site inhibitors is mediated by mutations Met423Thr and/or Ile482Leu in the thumb domain and mutations in the palm and finger domains (related to palm-site inhibitors), in agreement with previous reports (30,33,40).…”
Section: Discussionsupporting
confidence: 93%
“…Resistant replicons were selected using methodologies described previously (33,41). For the selection of dual resistance 1.5 ϫ 10 5 replicon cells were plated in 6-cm dishes in the presence of 0.5 mg/ml of G418 and in the absence or presence of inhibitors NNI-1 and NNI-3 in a checkerboard fashion at concentrations of 1ϫ, 5ϫ, or 10ϫ the IC 50 .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we demonstrate that the major in vitro resistant mutations against BILN 2061 remain fully susceptible to VX-950, and the dominant VX-950 resistance mutation is still sensitive to BILN 2061. In vitro resistance mutations against the HCV polymerase inhibitors have also been identified in the replicon system (39,40). These studies suggest that future hepatitis C therapy involving small molecule inhibitors of HCV enzymes might require multidrug combination, as in the case of the current HIV treatments.…”
Section: Discussionmentioning
confidence: 95%
“…The benzothiadiazine series, including NNI-1, was reported to select for major resistance mutations at amino acid positions Met 414 and Tyr 448 in the palm domain, which lies near the enzyme active site (35,36). Mapping of replicon cells resistant to HCV-796 identified specific mutations in NS5B involving changes at residues Cys 316 and Ser 365 at the palm binding site (8,24).…”
Section: Correlation Of Binding Affinity and Inhibition Potency Of Nomentioning
confidence: 99%